(untitled) (Iranian Journal of Kidney Diseases, 2015)
Introduction. Methotrexate, an antagonist of folic acid used in the treatment of many cancers and inflammatory diseases, is associated with side effects that limit its usage. Infliximab has been reported to have a protective effect against nephrotoxicity induced by some drugs and ischemic reperfusion. We aimed to investigate whether infliximab has a protective effect against methotrexate-induced nephrotoxicity. Materials and Methods. We administered methotrexate at a dose of 20 mg/kg as a single intraperitoneal injection in 10 rats (methotrexate group). Another group of 10 rats received a single dose of infliximab, 7 mg/kg, intraperitoneally (infliximab group). The methotrexate and infliximab group received a similar single injection of infliximab 72 hours prior to methotrexate injection. After 72 hours a single dose of methotrexate, 20 mg/kg, was administered intraperitoneally. Five days after methotrexate injection, blood samples were collected and the kidney tissues were removed for biochemical and histological examination. Results. The methotrexate group had significantly higher tissue levels of tumor necrosis factor-α (P = .008), interleukin-1β (P = .036), nitric oxide (P < .001), and adenosine deaminase (P < .001) than the methotrexate and infliximab group after the 5-day study. The methotrexate group also had significantly higher total histological scores (P < .001) and carbonic anhydrase-II activity (P < .001) when compared to the methotrexate and infliximab group. Conclusions. Infliximab has a strong protective effect against methotrexate-induced nephrotoxicity by suppressing cytokines release. It may decrease methotrexate-induced nephrotoxicity by regulating carbonic anhydrase-II enzyme activities and slowing down purine metabolism.